2017
DOI: 10.3892/ijo.2017.4091
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin induces apoptotic cell death via antioxidant activity in human colon cancer cells

Abstract: The present study determined whether luteolin induces HT-29 colon cancer cell death through an antioxidant effect such as the activation of antioxidant enzymes. Luteolin decreased cell viability in human colon cancer cells (HT-29), whereas it had no effect on normal colon cells (FHC). Luteolin induced apoptosis by activating the mitochondria-mediated caspase pathway in HT-29 cells. Luteolin caused loss of the mitochondrial membrane action potential, increased mitochondrial Ca2+ level, upregulated Bax, downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 48 publications
7
82
0
Order By: Relevance
“…Luteolin is a flavonoid that has been indicated to arrest the cell cycle and induce apoptosis in a variety of different cancer types (13,14,27). In the present study, the results of the MTT assay demonstrated that luteolin exhibited cytotoxicity on HT29 cell in a concentration-and time-dependent manner, which is consistent with the results of other studies (17,30).…”
Section: Discussionsupporting
confidence: 93%
“…Luteolin is a flavonoid that has been indicated to arrest the cell cycle and induce apoptosis in a variety of different cancer types (13,14,27). In the present study, the results of the MTT assay demonstrated that luteolin exhibited cytotoxicity on HT29 cell in a concentration-and time-dependent manner, which is consistent with the results of other studies (17,30).…”
Section: Discussionsupporting
confidence: 93%
“…CMAC is a GSH‐sensitive dye and commonly used to measure intracellular GSH levels correlated with glutathione peroxidase (GPx) activity (Kang et al, 2017). Blue CMAC staining showed a lower blue fluorescence intensity of GPx activity in cells treated with 0.5 mM ASA compared with the other groups, showing inactivation of the antioxidant system ( p < .05; Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed procedure was described elsewhere [13]. The antibodies against GTPBP4 (ab92342), TNFRSF10B (ab199357), MDM2 (ab16895), p53, CCND1 (ab134175), FAS (ab82419), PTEN (ab79156), CDKN1A (ab109520) and GAPDH (ab9485) were purchased from Abcam.…”
Section: Methodsmentioning
confidence: 99%